EPIDEMIOLOGICAL ASPECTS OF THE TUBERCULOSIS PATHOMORPHISM IN MODERN CONDITIONS - N. M. Koretskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Not only the growth of the death, rate and the morbidity rate can be considered as epidemiological manifestation. of the tuberculosis pathomorfism in modern conditions but also the changes of biological properties of the activator. Since 2003 till 2011 mycobacterium drug resistance with the patients with the newly diagnosed infiltrative tuberculosis which is of the most frequent occurrence has increased 1,4 times. The mycobacterium drug resistance has undergone the apparent qualitative changes. The percent of multidrug resistance has also increased. The combination of multidrug resistance and rescue therapy drug resistance has become more often. At the same time bacterioexcretin has become more profuse, mycobacterium growth rate has become slower and. the fact proves there is an interaction between two their biological properties - drug resistance and. growing power.